PENERAPAN CARA PENGOLAHAN PANGAN YANG BAIK PADA UMK ABON YUDHISTIRA KUPANG - Lalel, Herianus J. D.; Rubak, Yuliana Tandi; Abidin, Zainal; Cakswindryandhani, Ni Luh Putu Ravi; Nalle, Ryan Pieter I; Pollo, Roddialek; Radja Kana, Yenny; Oematan, Shirly S.; Neranai, Yohanes Franyklino; Gandut, Yosefina R.Y (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
The Certificate of Good Manufacturing Practices (GMP) is a regulatory requirement in Indonesia to ensure the quality and safety of food and beverage products. However, many micro, small, and medium enterprises (MSMEs) in Kupang City have yet to obtain CPPOB certification, largely due to limited knowledge and skills in meeting the necessary requirements. This community service program aimed to assist an MSME in implementing CPPOB standards through a series of activities, including surveys, production process assessments, coordination with stakeholders, and mentoring to improve production systems. UMK Abon Yudhistira, located in Naikoten II, Kupang City, was selected as the model enterprise. The intervention focused on redesigning the production room layout to reduce the risk of cross-contamination arising from the movement of raw materials, finished products, personnel activities, and external factors. In addition, product packaging information was revised to enhance traceability in accordance with CPPOB guidelines. The program resulted in significant improvements in production practices, enabling UMK Abon Yudhistira to successfully obtain CPPOB certification from the Indonesian Food and Drug Authority. This initiative demonstrates that targeted technical assistance can effectively support MSMEs in achieving compliance with national food safety and quality standards.